Plantwide simulation and sensitivity analysis of a palm oil fractionation process - Arshad Ahmad, 1963-; Ling, Leong Yau; Malaysian Technology Congress (2001 : Melaka) (Skudai : Universiti Teknologi Malaysia, 2001)
50